Expensive equipment and autonomour actors. Horses in Czech historical reenactment. - Řičář, Josef (Dějiny – teorie – kritika, 2025)
The paper examines the role of horses in Czech military historical reenactment. Combining the concepts of multispecies ethnography and reenactment studies, it focuses on non-human actors involved in various levels of reenactment practice and beyond. The presence of cavalry in battle reconstructions adds to the appeal of the show to the public and creates an authentic historical experience for the reenactors. Cavalry riders enjoy an exclusive social status within the reenactor milieu, but this comes at a high price. The high financial cost of horse ownership and the care that these animals require are just a few of the challenges these reenactors face. The paper also shows horses as autonomous participants in the historical reenactment. Employing non-human living creatures with different bodies but also intentions, fears, or cognitive functions presents another considerable challenge for the cavalry reenactors. Reenactors use specific training methods to achieve the ability of a horse to participate in the battle reconstruction, making it authentic and safe at the same time. By focusing on non-human agency, the paper offers a fresh analytical perspective for the emerging field of historical reenactment studies. In a broader framework, it argues for the importance of scholarly attention to non-human and human entanglements as well.